Program Aplikasi Lembur PT Aplikasi Karya Anak Bangsa (AKAB) Divisi GoPay Berbasis Website - Bintang Triawisesa (CV. Syntax Corporation Indonesia, 2021)
Overtime Application Program for PT. Aplikasi Karya Anak Bangsa, GO PAY Division. Thesis. Jakarta: Information Systems Study Program, School of Information and Computer Management (STMIK) Muhammadiyah Jakarta 2019. Constraints faced by employees of PT AKAB, the GO PAY division, every time they input overtime data, they must print the overtime form and manually input the overtime form. The occurrence of errors in inputting total overtime by the admin is also an obstacle that occurs. To overcome this we need an application program that can simplify the process of applying for employee overtime quickly and accurately. The system design made is a system application program design that is integrated with the website. The design of an overtime application program is based on UU RI No.13 of 2003. The initial step taken is to use the 'waterfall method', the phase begins with a needs analysis, design, system development, system testing and finally the maintenance of the system. This research is expected to make it easier for employees and admin staff to input overtime data and calculations, more valid time efficiency, cost and accuracy. In addition, it is also expected to help smooth administration in filing overtime documents.